Vulvovaginal candidosis caused by Candida non-albicans, proportion and clinical characteristics in the Dr. Cipto Mangunkusumo National General Hospital, Jakarta (Faculty of Medicine Universitas Indonesia, 2003)
The prevalence of vulvovaginal candidosis (VVC) caused by C. non-albicans tends to increase, recently. The aim of this study was to obtain data about proportion and clinical characteristic of C. non-albicans VVC at dr. Cipto Mangunkusumo General Hospital, Jakarta. This is a cross-sectional study on all female patients with symptoms of VVC visiting Obstetri-gynaecology and Dermatovenereology outpatient clinics at dr. Cipto Mangunkusumo General Hospital, Jakarta. All subjects had positive Gram stain, showed Candida spp. on culture with CHROMagar Candida, and had no other specific genital infections. Sixty nine subjects aged 26â44 years old (averaged 29 years old) were included in this study. Candida non-albicans was found in 30.4% subject, and consisted of: C. glabrata (61.9%), C. tropicalis (28.6%) and C. parapsilosis (9.5%). We found that C. non-albicans VVC infections are more common in women above 45 years old, using non-hormonal contraceptives, whose sexual partner has erythema and pruritus in glands penis, and having the disease for more than 1 year. No differences in clinical symptoms were noted between C. albicans and C. non-albicans infection. We concluded from this study that the proportion of C. non-albicans infections at dr. Cipto Mangunkusumo General Hospital, Jakarta, with C. glabrata represents the most prevalent species. No characteristic clinical symptoms were found from the subjects with C. non-albicans VVC when compared with those infected by C. albicans. (Med J Indones 2003; 12: 142-7)